Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.

Polybenzimidazole mediated N-doping along the inner and outer surfaces of a carbon nanofiber and its oxygen reduction properties - Balan, Beena K.; Manissery, Aiswarya Padinhare; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
Nitrogen-doped (N-doped) hollow carbon nanofiber (CNF) was synthesized by incorporating a nitrogen containing polymer precursor, polybenzimidazole (PBI-BuI), in the inner cavity as well as on the outer walls of the CNF, followed by a high temperature treatment. PBI-BuI incorporation along the inner and outer surface of the CNF was accomplished by synthesizing a low molecular weight polymer by tuning the synthetic parameters. The solution concentration of the PBI-BuI is also varied to facilitate its entry into the CNF by capillary action. The high temperature treatment (700-1000 degrees C) of the resulting CNF-PBI material decomposes the polymer and induces N-doping along the inner and outer surfaces of the CNF. The initial PBI-BuI content and the annealing temperature are also systematically varied to choose the right combination of starting precursors and heat-treatment conditions. Detailed X-ray photoelectron spectroscopy analysis of the samples shows that pyridinic-type nitrogen is the major component in all the samples. Electrochemical characterizations of this material using cyclic voltammetry, rotating disc electrode studies and durability analysis demonstrated that this material can act as a metal-free oxygen reduction electrocatalyst with improved oxygen reduction kinetics and stability. It is also revealed that the onset potential, limiting current density, number of transferred electrons, etc. have a strong dependence on the annealing temperature.

Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrids for improved supercapacitor performance - Balan, Beena K.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (RSC Advances, 2013)
Carbon nanofiber-RuO2-poly(benzimidazole) ternary hybrid electrode material which integrates dual wall decoration and interfacial area tuning for supercapacitor applications has been devised based on a simple approach. This is achieved by decorating RuO2 nanoparticles of size ca. 2-3 nm along the inner and outer walls of a hollow carbon nanofiber (CNF) support (F-20RuO(2)). In the next step, a proton conducting polymer, phosphoric acid doped polybenzimidazole (PBI-BuI), interface is created along the inner and outer surfaces of this material. A 103% increase in the specific capacitance is obtained for RuO2-PBI hybrid material as compared to that of F-20RuO(2) at the optimum level of the polymer wrapping. Apart from the high specific capacitance, the RuO2-PBI hybrid materials exhibit enhanced rate capability and excellent electrochemical stability of 98% retention in the capacitance. Such a remarkably high activity can be primarily attributed to the efficient dispersion of active sites achieved by properly utilizing inner and outer surfaces of CNF. Apart from this, the facile routes for ion transport created as a result of PBI incorporation coupled with excellent interfacial contact between the RuO2 and the electrolyte resulting in the improved utilization of the active material also contribute to the improved activity. In addition to this, the synergistic effects of pseudocapacitive contribution from both the PBI-BuI and RuO2 also contribute to the redefined performance characteristics.

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.

New approach of blending polymeric ionic liquid with polybenzimidazole (PBI) for enhancing physical and electrochemical properties - Rewar, Anita S.; Chaudhari, Harshal D.; Illathvalappil, Rajith; Sreekumar, K.; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
Although the use of ionic liquids (IL) in polymeric membranes is known to elevate the electrochemical performance for proton exchange membrane-based fuel cells (PEMFC), they suffer from drawbacks such as IL drain and lowering in mechanical properties that lead to deterioration in PEMFC performance. To mitigate these issues, we report, for the first time, the use of polymeric ionic liquid (PIL), namely, poly(diallyl dimethyl ammonium trifluoride methane sulphonate) (P[DADMA][TFMS]) to be blended with polybenzimidazole (PBI-I) as a membrane material for PEMFC. PBI-I and (P[DADMA][TFMS]) were chosen because they form miscible blends and are suitable for acid doping as a matrix, which can eventually be used as proton conductor. The structure, miscibility and inter-polymer interactions were studied by infrared (IR) spectroscopy and differential scanning calorimetry (DSC). The increase in proton conduction in comparison to the PBI membranes was observed due to the presence of ionic groups of PILs in blend membranes. With the increase in PIL content, the proton conductivity of the composite membranes gradually increased from 0.04 S cm(-1) for PBI to 0.07 S cm(-1) for the blend membrane at 150 degrees C. The MEAs were fabricated with PBI-I, PBI-PIL15, PBI-PIL25 and PBI-PIL35. Corresponding single cells were successfully tested at temperatures of 160 degrees C. The maximum power density and current density obtained were 515 mW cm(-2) and 1632 mA cm(-2), respectively, for PBI-PIL25-based MEA.

Chemically stable covalent organic framework (COF)-polybenzimidazole hybrid membranes: enhanced gas separation through pore modulation - Biswal, Bishnu P.; Chaudhari, Harshal D.; Banerjee, Rahul; Kharul, Ulhas K. (Chemistry-A European Journal, 2016)
Highly flexible, TpPa-1@PBI-BuI and TpBD@PBI-BuI hybrid membranes based on chemically stable covalent organic frameworks (COFs) could be obtained with the polymer. The loading obtained was substantially higher (50%) than generally observed with MOFs. These hybrid membranes show an exciting enhancement in permeability (about sevenfold) with appreciable separation factors for CO2/N-2 and CO2/CH4. Further, we found that with COF pore modulation, the gas permeability can be systematically enhanced.
Keywords: covalent organic frameworks; Gas separation; membranes; microporous materials; pore modulation

Preparation and investigations of ABPBI membrane for HT-PEMFC by immersion precipitation method - Chaudhari, Harshal D.; Illathvalappil, Rajith; Kurungot, Sreekumar; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole) (ABPBI) membranes were prepared by an easy and benign 'immersion precipitation' method; alleviating drawbacks of conventional solution casting method involving evaporation of the corrosive solvent. The importance of varying inherent viscosity on the properties of resulting membranes was investigated. The porous membranes formed by immersion precipitation method were analyzed for basic properties (water flux, porosity and dimensional analysis). Since the dense structure is required for their applicability for a fuel cell, through-porosity of the formed membranes was successfully eliminated using a unique shrinkage (similar to 50%) property of ABPBI, initially, at 60 degrees C followed by at higher temperature. The correlation of membranes annealing temperature with the mechanical properties, phosphoric acid doping and proton conductivity was established. The present membranes exhibited high doping level (5.1 mol/RU), proton conductivity (0.083 S cm(-1)) and fuel cell performance. For comparison, solution casted membranes were prepared and analyzed. The OCP (0.91 V) and max power density (766mWcm(-2)) are quite promising features of this new type of membranes.

Solvent and pH-stable poly(2,5-benzimidazole) (ABPBI) based UF membranes: preparation and characterizations - Lohokare, Harshada R.; Chaudhari, Harshal D.; Kharul, Ulhas. K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole), commonly known as ABPBI, is an excellent thermo-chemically stable polymer that is widely evaluated as a proton exchange membrane material in a fuel cell. Its niche intrinsic characteristics could be highly useful in the membrane preparation for various separation applications, especially under harsher environments. To gain insights towards this feasibility, ABPBI based supported membranes were prepared by phase inversion method. Effects of the nonwoven porous support material (polypropylene/polyester), non-solvent (water/0.5 N NaOH) and polymer concentration (6 or 4 wt%) on the membrane properties (water flux, rejection and porosity) were investigated. The stability of these membranes towards common organic solvents, concentrated acid (25 N H2SO4), base (2.5 N NaOH) and an autoclave condition was analyzed. ABPBI membrane showed a pore collapse after drying. In order to avoid this, the glycerol treatment was not only found to be suitable but also repeatable, without significant deviations in the water flux.
Keywords: ABPBI membrane; Pore size distribution; Solvent stable membranes; Ultrafiltration